Study on the Influence of Product Design Attributes on the Usage of Insecticide Treated Mosquito Nets in Kafue District, Zambia - Timothy Silweya; Charles Muwe Mungule (Modern Perspectives in Economics, Business and Management Vol. 4, 2021)
Purpose: The goal of this study was to look into the relationship between the colour, shape, and size of Insecticide Treated Nets (ITNs) and their use. Methodology: The research design for this study was mixed methods.. The study took place in the Nangong we and Kafue Mission Health Centre catchment regions in Kafue district. From a total of 300 households (HHs) with ITNs, 30 were randomly selected using a simple random sample technique. One HH was not reached due to heavy rains, reducing the sample size to 29 HHs. Quantitative data was collected through questionnaires, while qualitative data was gathered through Focus Group Discussions (FGDs). Multiple linear regression in excel was used to test the hypothesis that ITN attributes do not influence ITN usage. Findings: In this study, it was observed that majority of households owned between five to six ITNs. Most of the households reported that they have been using ITNs for over ten years. A further inquiry on the most preferred ITNs revealed that 100% of households liked nets that fit on a double bed followed by 86.2% which liked rectangular nets and the last category of 52% that favored white nets. The study hypothesized that colour, shape and size of ITNs do not influence usage. This hypothesis was tested using a multiple linear regression performed using Excel. The analysis of the test results showed that only 3.3% of the preference for ITN usage is explained by colour, shape and size with a P-value of 0.85. Since this statistic is greater than alpha 0.05 at 95% confidence level there is strong evidence not to reject the null hypothesis and conclude that ITN attributes are not major factors that limit usage of ITNs. Unique contribution to theory, practice and policy: This study demonstrated that systemic thinking using the limits to growth system theory can be used to explain weaknesses of linear thinking that has been used over the years by the Ministry of Health and other health communicators in developing health promotion strategies for prevention of malaria using ITNs. Over the years one key major message has been at the core of ITN promotion, “sleep under an ITN all year round to prevent mosquitoes that cause malaria”. Despite emphasis on this message, ITN use has been below 50% since 2006 while the corresponding knowledge on ITN use has been increasing to above 60%. Using the limits to growth theory demonstrated that there could be other factors than knowledge gaps that are responsible for low utilization of ITNs.